High throughput DNA sequencing to detect differences in the subgingival plaque microbiome in elderly subjects with and without dementia - Cockburn, Andrew F; Dehlin, Jonathan M; Ngan, Tiffany; Crout, Richard; Boskovic, Goran; Denvir, James; Primerano, Donald; Plassman, Brenda L; Wu, Bei; Cuff, Christopher F (Investigative genetics, 2012)
To investigate the potential association between oral health and cognitive function, a pilot study was conducted to evaluate high throughput DNA sequencing of the V3 region of the 16S ribosomal RNA gene for determining the relative abundance of bacterial taxa in subgingival plaque from older adults with or without dementia. Subgingival plaque samples were obtained from ten individuals at least 70 years old who participated in a study to assess oral health and cognitive function. DNA was isolated from the samples and a gene segment from the V3 portion of the 16S bacterial ribosomal RNA gene was amplified and sequenced using an Illumina HiSeq1000 DNA sequencer. Bacterial populations found in the subgingival plaque were identified and assessed with respect to the cognitive status and oral health of the participants who provided the samples. More than two million high quality DNA sequences were obtained from each sample. Individuals differed greatly in the mix of phylotypes, but different sites from different subgingival depths in the same subject were usually similar. No consistent differences were observed in this small sample between subjects separated by levels of oral health, sex, or age; however a consistently higher level of Fusobacteriaceae and a generally lower level of Prevotellaceae was seen in subjects without dementia, although the difference did not reach statistical significance, possibly because of the small sample size. The results from this pilot study provide suggestive evidence that alterations in the subgingival microbiome are associated with changes in cognitive function, and provide support for an expanded analysis of the role of the oral microbiome in dementia.